2010
DOI: 10.4049/jimmunol.1000824
|View full text |Cite
|
Sign up to set email alerts
|

Existence of CD8α-Like Dendritic Cells with a Conserved Functional Specialization and a Common Molecular Signature in Distant Mammalian Species

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
109
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 64 publications
10
109
0
1
Order By: Relevance
“…However, it has recently been shown that the CD8 1 cDCs in mouse and the BDCA3 1 cDCs in human blood uniquely express XCR1. 21,31,32 The cultured CLEC9A 1 DC also expressed this molecule (Figure 1d). CLEC9A is therefore unique to spleen and blood CD141 1 DCs 16,24 and was thus used as a marker to distinguish this subset in subsequent experiments.…”
Section: Resultsmentioning
confidence: 88%
“…However, it has recently been shown that the CD8 1 cDCs in mouse and the BDCA3 1 cDCs in human blood uniquely express XCR1. 21,31,32 The cultured CLEC9A 1 DC also expressed this molecule (Figure 1d). CLEC9A is therefore unique to spleen and blood CD141 1 DCs 16,24 and was thus used as a marker to distinguish this subset in subsequent experiments.…”
Section: Resultsmentioning
confidence: 88%
“…We focused on Xcr1, Clec9a, Cadm1, Clnk, and Rab7b (5430435G22Rik), because these genes are expressed selectively in CD8a + -type DCs from mouse spleen, human blood, and sheep lymph (4,5). CLEC9A, XCR1, and CADM1 contribute to confer their specific functions on spleen CD8a + DCs by promoting the cross-presentation of dead cell-associated Ags, the priming of CD8 + T cells, and the induction of IL-22 in CD8 + T cells (6,10,15,16).…”
Section: Lt-resident Cd8amentioning
confidence: 99%
“…This marker, the chemokine receptor XCR1, is also specifically expressed by human blood BDCA3 + DCs and sheep lymph CD26 + DCs and conserved during evolution (5,6). Thus, the community of the researchers working on DCs may consider using the term "XCR1 + DCs" to designate CD8a + -type DCs in a consistent manner across all mammalian species and tissues to further implement the definition of a universal nomenclature for mouse and human DC subsets (19).…”
Section: Lt-resident Cd8amentioning
confidence: 99%
See 2 more Smart Citations